Origins of the Karl Rahner Society - Masson, Robert (Philosophy & theology, 2020)
This article describes the origin in 1991 of the Karl Rahner Society, which meets every year within the annual convention of the Catholic Theological Society of America. The Rahner Society's origins include the role of William M. Thompson-Uberuaga as Founding Coordinator, the contributions of the earliest members of the Coordinating Committee, and the relation between the KRS and the CTSA. Society members found a vehicle for publication in the Marquette University journal Philosophy & Theology whose founding editor was Andrew Tallon. The journal continues to publish the society's "Rahner Papers" annually.